Appraising research in second language learning : a practical approach to critical analysis of quantitative research - Porte, Graeme Keith (Language learning and language teaching, 2010)
Designed for students of applied linguistics and second language acquisition on research training courses, practising language teachers, and those in training, this combination textbook/workbook is a set or recommended textbook on more than a hundred undergraduate and postgraduate courses worldwide. Now in its second edition, it remains the only book to provide specific advice and support to those wishing to learn a methodical approach to the critical analysis of a research paper. It seeks to answer a current need in the literature for a set of procedures that can be applied to the independent.